MOTIVES FOR MURDER BASED ON NEWS IN ONLINE MEDIA KOMPAS.COM IN 2023 FROM A LEGAL SOCIOLOGY PERSPECTIVE - Muryanti, Muryanti (Jurnal Sosiologi Dialektika Sosial, 2024)
The number of murder crimes is decreasing from year to year which can be caused by various things. The motive for murder can be categorized into 2, namely; (1) internal motives, namely motives related to the biological and psychological condition of the perpetrator, and (2) external motives, economic conditions (unable to return capital, unequal distribution of wealth), conflict, family disharmony, promiscuity, nightlife, infidelity, wrong parenting, taking advantage of circumstances to take advantage and make political decisions, the environment, technology, religion, spectacles, reading, culture, ideology, population density, unequal distribution of culture, neglect and educating children. This article aims to findout about the motives for murders that occurred during 2023. The theory used to analyze is legal sociology related to the factors that cause crime and the rationality that causes someone to carry out murder motives. The results of the research show that based on criminal reporting published on kompas.com in 2023, 21 murder cases showed that the perpetrators of the murder were 100% men with an age range of 14-57 years, while the victims were 48% women and 52% men with a range of aged between 12-57 years. The motive for murder was caused by 57% economic motives; 33% were caused by psychological motives and 10% were caused by shamanic motives. The categorized data shows that the motive for the murder committed by the victim in 2023 is not much different from the previous year, that economic factors were the most dominant cause of the murder. As with the course of criminal history, the most dominant cause is economic factors. The motive for murder is very complex, considering that economics as the main motive for murder means instrumental rationality as the main reason. This shows that crime is closely related to the economic conditions of society.